EVALUASI PROGRAM REVITALISASI PASAR TRADISIONAL REJOMULYO DI KOTA SEMARANG - Triatmojo, Muhamad Bambang; Rengga, Aloysisus (Journal of Public Policy and Management Review, 2019)
The Rejomulyo market revitalization program is an activity to improve the image of the market that previously slum, dirty and muddy for the better. The main reason for revitalizing the Rejomulyo market is the market conditions that are already inadequate and not in accordance with the standards of the public market and healthy markets, as well as the old market land use plans that will be used as the Green Open Space. The new Rejomulyo market is expected to be a clean, orderly, safe and healthy market, so that its existence can compete with the modern market. The implementation of the program was challenged by a number of traders who refused to move, so the program has not been completed to date. The purpose of this study is to Evaluate the Rejomulyo market revitalization program and to identify obstacles to the implementation of the program. This study uses qualitative descriptive method, in order to achieve the research objectives , the CIPP (Context, Input, Process and Product) program evaluation models and the implementation models of George C. Edward III are used. The result of the study found that the Rejomulyo market revitalization program was still not optimal. That is seen from the context of the program that is not optimal, because in the program planning does not involve traders. The context of the program that is not optimal, makes the process and product of the program has not been optimal, even though the program input is good. In addition, it was found that the factors that inhibited the Rejomulyo market revitalization program were, communication of that program was less effective, less optimal resources, poor disposition and inappropriate SOPs(Standard Operating Procedure). For that advice that researcher gives is to reviews the existing SOPs on traditional market development so the involvement of traders becomes clear and it is necessary to immediately move traders who have not yet moved, and hold discussions for future market management